THE COMBINED INFLUENCE OF LEARNING MOTIVATION AND PARENTAL INVOLVEMENT ON VOCATIONAL HIGH SCHOOL STUDENTS' ACHIEVEMENT IN OPERATING SYSTEM COURSES - Moh Gufron; Jonantan Vicky Robet Bagaswara (JoEICT (Jurnal of Education And ICT), 2026)
Information and communication technology (ICT) education in Indonesian junior secondary schools has traditionally relied on lecture-based instruction, a format that affords learners limited opportunity for active engagement and often fails to translate into optimal learning outcomes. This study investigated whether an online-adapted demonstration method produced significantly different learning outcomes compared with a conventional lecture-based method among grade VII students studying basic Microsoft Word operations at a public junior secondary school (SMPN 2 Pakel) in Tulungagung, Indonesia, during the transition to remote instruction necessitated by the COVID-19 pandemic. A quantitative, quasi-experimental approach employing a nonequivalent pretest-posttest control-group design was adopted. From a population of 94 grade VII students, 62 students were selected through purposive sampling and assigned to an experimental class (n = 31), which received video-based demonstration instruction distributed through a class messaging group and a video-sharing platform, and a control class (n = 31), which received conventional text- and lecture-based instruction through the same digital channels. Achievement was measured using a validated multiple-choice test administered before and after treatment, and an independent-samples t-test was used to examine between-group differences once normality and homogeneity assumptions were confirmed. The mean posttest score of the experimental group (M = 83.06, SD = 7.49) exceeded that of the control group (M = 65.65, SD = 9.46); the independent-samples t-test indicated a statistically significant difference, t(60) = 8.035, p .001, mean difference = 17.42. These findings demonstrate that the online demonstration method produced a significantly larger improvement in learning outcomes than the conventional method, supporting multimedia- and constructivist-learning perspectives that visualized, sequential demonstration facilitates deeper comprehension of procedural ICT content even in a fully remote setting. The study contributes empirical evidence on adapting an inherently visual, hands-on teaching method to emergency remote instruction—an area that remains underexplored relative to research on demonstration teaching in face-to-face classrooms. Implications for ICT pedagogy, methodological limitations, and directions for future research are discussed.